2020
DOI: 10.1029/2019gl086799
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Multidomain Overlaps and Grand Ensemble Generation in CORDEX Regional Projections

Abstract: The Coordinated Regional Climate Downscaling Experiment (CORDEX) initiative has made available an enormous amount of regional climate projections in different domains worldwide. This information is crucial for the development of adaptation strategies and policy‐making. A relevant open issue in this context is assessing the potential multidomain conflicts that may result in overlapping regions and developing appropriate ensemble methods trying to make the most of all available information. This work addresses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Large multimodel and multiscenario ensembles are expected to add value and provide a more representative range of possible futures [7,49]. In this respect, downscaling of multiple global models and future pathways or scenarios are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Large multimodel and multiscenario ensembles are expected to add value and provide a more representative range of possible futures [7,49]. In this respect, downscaling of multiple global models and future pathways or scenarios are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The regional warming is found to follow a differential seasonal response with a much stronger temperature increase projected for the boreal summer compared to the rest of the year 4 . As a result of the rising warm-season temperatures, heatwaves can be expected to increase in frequency, magnitude, and duration [5][6][7][8] . The observed trends in heat extremes corroborate the model simulations and the transition to much warmer conditions, which started in the 1980s [9][10][11][12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Similar multi-domain approaches have already been used for different regions, e.g. by Zittis et al (2019) and Legasa et al (2020).…”
Section: Climate Datamentioning
confidence: 99%
“…Following Spinoni et al (2020) we define that the change in an index is significant in sign if two-thirds of simulations agree on the sign of change, significant in magnitude if the ensemble median change is larger than the inter-model variability over 1981-2010, robust if the change is both significant in sign and magnitude, uncertain if the change is not significant in sign nor in magnitude. Results are shown at different aggregation scales: global, continental, and macro-regional, and macro-regions are defined according to Iturbide et al (2020) and are shown in FigureS2 of SM.…”
Section: Drought Hazard Indicators and Derived Parametersmentioning
confidence: 99%